Avaliação da Plataforma Lattes como fonte de coleta de metadados para povoamento automatizado em repositórios institucionais - Sarvo, Denilson de Oliveira (2018)
Institutional Repositories (IR) are related to the Green Road strategy adopted by the Open Access Movement, which aims to create digital archives for storing and providing access to scientific and technological information. IR bring benefits such as the elimination of barriers to information access, enhancement of visibility and preservation, and also appear as a strategic source for the development of indicators of institutional scientific production. Their implementation is associated with technological, human, political and managerial aspects, and a crucial factor for this is ensuring that they are populated with data. This process comprehends collection, insertion, validation and provision of full text publications in their collections. Actions intended to populate IR have shown themselves ineffective in face of the difficulties to retrieve institutional scientific production, partly indexed on scientific and technological information databases. Facing the hypothesis that the Lattes Platform might minimize deficiency in the retrieval of scientific production of higher education institutions, this study aimed to assess the capacity to retrieve metadata from the Lattes Platform, comparing it to Web of Science, Scopus and SciELO databases. For the sake of comparison, a case study was conducted, our unit case being the Federal University of São Carlos (UFSCar). We have utilized the SyncLattes tool for obtaining the registers that constitute the analyzed sample, and have applied bibliometry as our method of analysis. The results obtained comprise: 1) the retrieval of the scientific production from UFSCar registered in the Lattes Platform; 2) identification of the share of registers from the Lattes Platform also indexed on the Web of Science, Scopus and SciELO databases; 3) identification of UFSCar publications in open access sources; and 4) the assignment of the embargo factor on the registers retrieved. It has been concluded that the Lattes Platform is a metadata collection source that is strategic for populating IR, since it alone has guaranteed the coverage of a significant share of the scientific production in the unit-case analyzed.